Path Loss Models for 5G Wireless Communication System Using mmWave Communication Channel - Dawood, Zinah (Al-Khwarizmi Engineering Journal, 2025)
Multiple-input multiple-output (MIMO) antenna topologies in wireless communication systems can increase channel capacity and dependability. The use of millimeter (mm)-wave frequency bands in conjunction with other technologies is a substantial step in achieving high data rates for sophisticated AI and multimedia devices. However, transmitting mm wave frequency signals presents challenges such as fading, time delay, propagation and scattering loss. Therefore, optimising propagation parameters is critical to improving performance. This paper examines the influence models for path loss (PL): ABG and CI on the design and analysis of a 4×4 MIMO W-OFDM system employing 16-QAM modulation technique for 5G wireless communication. This paper examines the  system  using the CI and ABG  PL models to assess PL in dB, normal distribution and standard deviation. This paper uses 16-QAM digital modulation, and the simulation results show that the CI PL model-based MIMO W-OFDM system is very robust and successful in signal recovery.